Growth and Photoacclimation Strategies of Three Zostera Species Along a Vertical Gradient: Implications for Seagrass Zonation Patterns - Park, Sang Rul; Moon, Kyeonglim; Kim, Seung Hyeon; Lee, Kun-Seop (Frontiers in Marine Science, 2021)
Seagrasses typically display vertical zonation patterns in tropical and temperate areas. In East Asia, three Zostera species (Z. japonica, Z. marina, and Z. caespitosa) are distributed at different water depths, leading to zonation patterns from intertidal to subtidal zones. The present study aimed to determine whether these patterns could be explained by differences in their physiological responses, morphological traits, and meadows architecture caused by depth variations. Intertidal Zostera japonica had the lowest shoot height and blade width and the highest shoot density, while subtidal Z. caespitosa exhibited the largest specific leaf area. Total carotenoid content and the total chlorophyll/total carotenoid ratio were significantly higher in Z. japonica than in Z. marina or Z. caespitosa. The average carbon stable isotope (δ13C) values were significantly less negative in Z. caespitosa than in Z. marina and Z. japonica. The average maximum relative electron transport rate was higher for Z. marina than for Z. japonica and Z. caespitosa, while the maximum quantum yield values were higher for Z caespitosa than for Z. japonica and Z. marina. The non-photochemical quenching (NPQ) of Z. japonica extinguished within 5-min following the rapid light curve, indicating that most of its NPQ was energy-dependent quenching (qE). The rapid light curve (RLC) parameters and leaf relaxation after RLC showed that Z. japonica is a high-light adapted species and Z. caespitosa is a low-light adapted one. Additionally, Z. caespitosa showed the lowest dark respiration values and Z. japonica, the highest, suggesting that Z. caespitosa can survive with low photosynthetic activity. These results suggested that interspecific variations in the morphological and physiological characteristics, photosynthetic pigments, and meadows architecture of three Zostera species were associated with vertical zonation patterns and likely explain their patterns.